New species and record in the genus Carbacanthographis (lichenized Ascomycota, Graphidaceae) from China - Jiang, Shu-Hao; Hao, Cheng-Yue; Zhao, Xin; Jia, Ze-Feng (Phytotaxa, 2024)
During our research on the lichen genus Carbacanthographis from China, two species new to science were discovered in materials from Yunnan and Guangxi Provinces, i.e. Carbacanthographis crassibasalia sp. nov. with a corticate thallus, a completely carbonized excipulum, warty periphysoid tips, hyaline, muriform, 6–18 × 3–4-septate ascospores, and protocetraric acid and C. yunnanensis sp. nov. with an ecorticate thallus, a completely carbonized excipulum, warty periphysoid tips, hyaline, small, submuriform 4–6 × 0–1-septate ascospores and the presence of protocetraric acid. A new record for China, C. iriomotensis, collected in Hainan Province is also reported. Detailed morphological descriptions as well as high-resolution photographs of the morphology and anatomy of the three species are provided. A working key to all the known Carbacanthographis species from China is also provided.